Analisis Bahasa Perempuan dalam Film Cruella (2021) - Sovi Nur Asofia Rizki; Abd. Hanan EF; Erfan Muhammad Fauzi (Madah: Jurnal Bahasa dan Sastra, 2022)
According to the stereotype of gendered language, each gender tends to keep particular aspects of the language features they employed. Additionally, most men are thought to be less talkative than women. The Cruella de Vill movie is an example of how the film business has been influenced by how society views women and how they speak. by using qualitative research methods and based on the theory of Women's Language Features from Lakoff (Lakoff 2004), the researchers found a number of data on women's language features that appear in the film Cruella. Of the 102 data obtained, 30.3% of them are intensifiers, making them the most frequently used features, then super polite forms and avoidance of strong-swear words with 0.98% each being the least used. meanwhile precise color terms and hypercorrect grammar don't appear at all in the movie.